2016
DOI: 10.1021/acsami.6b02733
|View full text |Cite|
|
Sign up to set email alerts
|

Formation of Hierarchical Structure Composed of (Co/Ni)Mn-LDH Nanosheets on MWCNT Backbones for Efficient Electrocatalytic Water Oxidation

Abstract: Active, stable, and cost-effective electrocatalysts are attractive alternatives to the noble metal oxides that have been used in water splitting. The direct nucleation and growth of electrochemically active LDH materials on chemically modified MWCNTs exhibit considerable electrocatalytic activity toward oxygen evolution from water oxidation. CoMn-based and NiMn-based hybrids were synthesized using a facile chemical bath deposition method and the as-synthesized materials exhibited three-dimensional hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 45 publications
3
70
0
Order By: Relevance
“…When hydroxyl act as weak field ligands, Mn 3 + are in the high spin state, which leading to instability of NiMn LDH, Mn 3 + are easily oxidized to Mn 4 + , we can also observe that the characteristic peak of Mn 4 + exists at 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 around 647 eV. [28,[35][36][37] Additionally, the EDS mapping of UNML nanosheets ( Figure S2a-d) shows the homogeneous distribution of Ni, Mn and O elements.…”
Section: Resultsmentioning
confidence: 73%
“…When hydroxyl act as weak field ligands, Mn 3 + are in the high spin state, which leading to instability of NiMn LDH, Mn 3 + are easily oxidized to Mn 4 + , we can also observe that the characteristic peak of Mn 4 + exists at 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 around 647 eV. [28,[35][36][37] Additionally, the EDS mapping of UNML nanosheets ( Figure S2a-d) shows the homogeneous distribution of Ni, Mn and O elements.…”
Section: Resultsmentioning
confidence: 73%
“…The disappeared (001) peaks in LDH‐rGO may be due to the uniformly dispersion of graphene sheets and the very low content of GO. Moreover, compared with pure LDHs, a decrease in the intensity of the (003) reflection peak in LDH‐rGO hybrids shows a disordered layered structure .…”
Section: Resultsmentioning
confidence: 95%
“…The high OER catalytic activity of this material was attributed to the strong interaction of LDH with CNT through the formation of M‐O‐C (M=Ni, Fe) bonds, leading to the promotion of charge transport. Similar studies on hybridization of LDHs with conductive carbon materials have been reported, such as Ni‐Fe‐LDH/graphene composite, Co‐Mn‐LDH/CNT composite, (Co/Ni)‐Mn‐LDH/CNT composite, Ni‐Co‐LDH/carbon paper . The 2D nanosheets of TMOs, TMDs, and transition metal phosphides with high surface area and defects have also been used as efficient OER electrocatalysts.…”
Section: Electrode and Electrocatalyst Applicationsmentioning
confidence: 99%